Penggunaan Terapi Komplementer pada Orang dengan Lupus di Sumatera Selatan - Dian Wahyuni; Eddy Mart Salim; Nova Kurniati; Eka Yulia Fitri,; Khoirul Latifin (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2023)
specific parts and in general, which are called Lupus Erythematosus Systems. Research on the use of complementary therapies in Odapus is still limited. The purpose of this study was to determine the type of complementary therapy used by Odapus in South Sumatra. Descriptive research design, at the South Sumatra Lupus Association, total sampling. The results are as follows for the characteristics of respondents: by 96% of women, 88% of adults, and 68% used Complementary therapies. This study used seven types of complementary therapy, but the most used for Odapus were only three types, namely exercise therapy in the form of walking and cycling, which are physical activities that can improve blood flow and reduce cytokines that can trigger inflammation. Sholat and Do’a, two types of spiritual therapy, provide psychological peace so that the body relaxes, Odapus is not stressed, and does not release corticosteroid hormones to prevent recurrence. The three traditional medical therapies are in the form of using herbs, which must be communicated with health workers because some herbs are immunostimulatory, so Odapus cannot be consumed, and there are herbs that have anti-inflammatory properties. In conclusion, most Odapus in South Sumatra use complementary therapy. The type of complementary therapy that is widely used is exercise therapy in the form of walking and cycling, spiritual therapy with prayer, and traditional healing therapy using herbs.